A comprehensive defect study of tungsten disulfide (WS2) as electron transport layer in perovskite solar cells by numerical simulation - Sobayel K.; Akhtaruzzaman M.; Rahman K.S.; Ferdaous M.T.; Al-Mutairi Z.A.; Alharbi H.F.; Alharthi N.H.; Karim M.R.; Hasmady S.; Amin N. (Elsevier B.V., 2023)
In this study, an ideal planar perovskite solar cell (PSC) has been proposed and simulated by using Tungsten Disulfide (WS2) as an electron transport layer (ETL). Effects of various amphoteric defect states of PSC based on CH3NH3PbI3?xXx absorber layer and the interface properties of both ETL and hole transport layer (HTL) are quantitatively analysed by SCAPS-1D numerical simulator. Results show that the device performance is highly influenced by amphoteric defects in the absorber layer rather than the interface defects layer (IDL). It is also revealed that the quantitative tolerable range in CH3NH3PbI3?xXx and IDLs are less than 1015 cm?3 and 1016 cm?3, respectively. The PSC exhibits better performance in the range of 10 C40 C and degrades gradually at higher temperature. With the proposed structure, the simulation finds the highest power conversion efficiency (PCE) of PSC to be 25.70% (Voc = 1.056 V, Jsc = 25.483 mA/cm2, and FF = 88.54%). 2018